Highly Stable and Reactive Platinum Single Atoms on Oxygen Plasma‐Functionalized CeO2 Surfaces: Nanostructuring and Peroxo Effects. Issue 20 (16th March 2022) - Wan, Weiming; Geiger, Julian; Berdunov, Nikolay; Lopez Luna, Mauricio; Chee, See Wee; Daelman, Nathan; López, Núria; Shaikhutdinov, Shamil; Roldan Cuenya, Beatriz
Abstract: Atomically dispersed precious metals on oxide supports have recently become increasingly interesting catalytic materials. Nonetheless, their non‐trivial preparation and limited thermal and environmental stability constitutes an issue for their potential applications. Here we demonstrate that an oxygen plasma pre‐treatment of the ceria (CeO2 ) surface serves to anchor Pt single atoms, making them active and resistant towards sintering in the CO oxidation reaction. Through a combination of experimental results obtained on well‐defined CeO2 films and theory, we show that the O2 plasma causes surface nanostructuring and the formation of surface peroxo (O2 2− ) species, favoring the uniform and dense distribution of isolated strongly bonded Pt 2+ atoms. The promotional effect of the plasma treatment was further demonstrated on powder Pt/CeO2 catalysts. We believe that plasma functionalization can be applied to other metal/oxide systems to achieve tunable and stable catalysts with a high density of active sites. Abstract : Pre‐treatment of the ceria (CeO2 ) surface with oxygen plasma assists the formation of highly dense and stable Pt single atoms resistant to sintering under CO oxidation conditions. The effect is assigned to plasma‐induced oxide nanostructuring and the formation of surface peroxo species which favor single‐atom metal adsorption. This approach can be utilized for the preparation of stable single‐atom catalysts with a high density of active sites.